Predictability of indicators in local activation time mapping of ablation success for premature ventricular contractions - Takahiko Nagase; Takafumi Kikuchi; Shun Akai; Masafumi Himeno; Ryo Ooyama; Yoshinori Yoshida; Chiyo Yoshino; Takafumi Nishida; Takahisa Tanaka; Mitsunori Ishino; Ryuichi Kato; Masao Kuwada (Journal of Arrhythmia)
Abstract Introduction Differences in predictability of ablation success for premature ventricular contractions (PVCs) between earliest isochronal map area (EIA), local activation time (LAT) differences on unipolar and bipolar electrograms (⊿LATBi‐Uni), LAT prematurity on bipolar electrograms (LATBi), and unipolar morphology of QS or Q pattern remain unclear. We verified multiple statistical predictabilities of those indicators of ablation success on mapped cardiac surface. Methods Thirty‐five patients with multiple PVCs underwent catheter ablation after LAT mapping using multipolar mapping catheters with unipolar‐based annotation. Patients were divided into success and failure groups based on ablation success on mapped cardiac surfaces. Discrimination ability, reclassification table, calibration plots, and decision curve analysis of 10 ms EIA (EIA10ms), ⊿LATBi‐Uni, and LATBi were validated. Unipolar morphology was compared between success and failure groups. Results Right ventricular outflow tract, aortic cusp, and left ventricle were mapped in 17, 10, and 8 patients, respectively. In 14/35 (40%) patients, successful ablation was performed on mapped cardiac surfaces. Area under the curve of receiver‐operating characteristic curve of EIA10ms, ⊿LATBi‐Uni, and LATBi were 0.874, 0.801, and 0.650, respectively (EIA10ms vs. LATBi, p =.014; ⊿LATBi‐Uni vs. LATBi, p =.278; EIA10ms vs. ⊿LATBi‐Uni, p =.464). EIA10ms and ⊿LATBi‐Uni demonstrated better predictability, calibration, and clinical utility on reclassification table, calibration plots, and decision curve analysis than LATBi. Unipolar morphology of QS or Q pattern did not correlate with ablation success (p =.518). Conclusion EIA10ms and ⊿LATBi‐Uni more accurately predict ablation success for PVCs on mapped cardiac surfaces than LATBi and unipolar morphology.